The privatization of hope Ernst Bloch and the future of Utopia - Thompson, Peter 1960 July 22-; Žižek, Slavoj (SIC, 2013)
Bloch and a philosophy of the proterior / by Wayne Hudson -- An anti-humanist Utopia? / by Vincent Geoghegan -- Ernst Bloch's dialectical anthropology / by Johan Siebers -- Religion, Utopia, and the metaphysics of contingency / by Peter Thompson -- The privatization of eschatology and myth : Ernst Bloch vs. Rudolph Bultmann / by Roland Boer -- The education of hope : on the dialectical potential of speculative materialism / by Catherine Moir -- Engendering the future : Bloch's utopian philosophy in dialogue with gender theory / by Caitríona Ní Dhúill -- The zero-point : encountering the dark emptiness of nothingness / by Frances Daly -- A Marxist poetics : allegory and reading in The Principle of Hope / by David Miller -- Singing summons the existence of the fountain : Bloch, music, and Utopia / by Ruth Levitas -- Transforming utopian into metopian systems : Bloch's principle of hope revisited / by Rainer E. Zimmermann -- Unlearning how to hope : eleven theses in defense of liberal democracy and consumer culture / by Henk de Berg -- Can we hope to walk tall in a computerized world of work? / by Francesca Vidal and Welf Schröter